ANALISIS MEDIA PEMBELAJARAN BERBASIS VISUAL DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS V - Marisa, Anna; Al Haddar, Gamar; Salim, Nur Agus (SISTEMA: Jurnal Pendidikan, 2020)
The background of this research was the methods and strategies in conveying the materials. Besides, teacher used visual-based learning media in the teaching learning process adjusted to the material delivered by teacher. The data collection techniques used in this research was interview, and documentation. The data analysis used in this study was data collection, reduction, data presentation, and conclusions. To check the validity of data, it used source triangulation. The research found that the use of visual-based learning media for students class VA could improve the learning outcomes, it was seen from materials given by the teachers such as map in Social Science (IPS) lessons, Science (IPA) lessons on human body, human and animal digestive systems, human and animal respiratory systems, animal breeding system. For Civics lessons, it used Pancasila image for the basic material about Republic of Indonesia, and the cultures that existed in Indonesia. It was chosen because visual media could trigger students’ motivation and attracted their attention. The conclusion of this research was that the use of visual-based had been well-implemented.